Mídias Digitais como Ferramentas para Promover o Pensamento Computacional e Reduzir a Diferença de Gênero em Computação - Esteves, Lara Oliveira; Daniel, Luiza Caldeira; Silva, Sarah Cristina F. da; Guimarães, Maria Luísa R.; Quintela, Bárbara de Melo; Oliveira, Alessandreia Marta de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
The present work describes an institutional extension project initiative that, in addition to offering a playful approach to Computing for elementary school girls, also utilizes social media to disseminate the actions carried out by female students and professors, share accessible content about Computing, and feature profiles of relevant women in the field across various digital media. The project provides representation by involving female professors and mentors (undergraduate students) with the aim of breaking gender stereotypes and attracting more girls to Computing and related fields. A survey conducted with some of the undergraduate students involved in the project indicates that this type of project can also encourage women to remain in the field of Computing after entering higher education.